Sinonasal Inverted Papilloma - Thapa, N; Pradhan, B (Journal of Institute of Medicine Nepal, 2013)
Introduction: Sinonasal inverted papilloma is a rare tumour comprising about 0.5-4% of total nose and paranasal sinus tumours. Though various factors have been implicated its exact cause is unknown. This longitudinal, prospective study was carried out to nd out demographical prole, association of this tumour with smoking, occupation, variation with ethnic races and outcome of surgery. Methods: This study was carried out in the department of ENT-HNS, Tribhuvan University Teaching Hospital, Maharajgunj, Kathmandu from April, 2005 to March, 2011. Result: Out of 34 patients, there were 25 male and 9 female with ratio of 2.78:1. Age of the patients ranged from 14-76 years with median age of 51.5±2.74 SE years. Disease was more common in 4th to 7th decade. It was common in farmers (20). Eighteen patients were smoker and 16 nonsmoker. The disease was more common in mongoloids than in Indo-aryans. Out of 16 patients having stage III disease, 9 were smoker and 7 nonsmoker. Eighteen patients underwent endoscopic medial maxillectomy and 15 patients underwent medial maxillectomy via lateral rhinotomy approach. One patient who had bilateral disease underwent medial maxillectomy via lateral rhinotomy on the left side and endoscopically on the right side. There was recurrence of tumour in 2 patients who underwent surgery via lateral rhinotomy approach whereas in 1 patient who underwent surgery endoscopically. Conclusion: This study showed that sinonasal inverted papilloma was common in mongoloids than in Indo-aryans and farmers but no association with smoking. Endoscopic medial maxillectomy has less reccurence of tumour in comparison to lateral rhinotomy approach. DOI: http://dx.doi.org/10.3126/joim.v34i2.9044 Journal of Institute of Medicine August, 2012; 34:2 10-13